2012
DOI: 10.1182/blood-2012-01-401885
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of TMPRSS6 attenuates the phenotype in a mouse model of β-thalassemia

Abstract: Inappropriately low expression of the key iron regulator hepcidin (HAMP) causes iron overload in untransfused patients affected by ␤-thalassemia intermedia and Hamp modulation provides improvement of the thalassemic phenotype of the Hbb th3/؉ mouse. HAMP expression is activated by iron through the bone morphogenetic protein (BMP)-son of mothers against decapentaplegic signaling pathway and inhibited by ineffective erythropoiesis through an unknown "erythroid regulator." The BMP pathway is inactivated by the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 46 publications
11
134
0
1
Order By: Relevance
“…Amelioration of anemia in this mouse model probably requires higher hepcidin levels and mild iron restriction, which may act to limit a-globin synthesis and reduce the imbalance with b-globin synthesis. 8,18 Extrapolation of these findings to humans with b-thalassemia must take into account important differences in their iron metabolism , Th3/1 mice compared with Th3/1 mice at the age of 6 and 12 weeks. No difference was observed at 3 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amelioration of anemia in this mouse model probably requires higher hepcidin levels and mild iron restriction, which may act to limit a-globin synthesis and reduce the imbalance with b-globin synthesis. 8,18 Extrapolation of these findings to humans with b-thalassemia must take into account important differences in their iron metabolism , Th3/1 mice compared with Th3/1 mice at the age of 6 and 12 weeks. No difference was observed at 3 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…15 Infusions of apotransferrin were shown to ameliorate anemia in a model of mild thalassemia intermedia (th1/th1). 16,17 In the Th3/1 model, moderate increase in hepcidin, caused by transgenic hepcidin overexpression, 8 knockdown of the negative hepcidin regulator matriptase 2, 18,19 or administration of hepcidin agonists, 20 not only decreased iron loading but also improved anemia. 21 The hematological benefits of mild iron restriction seem to be the result of decreased a-globin precipitation, lower reactive oxygen species levels, and decreased apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…154,157 Interestingly, lack of Tmprss6 in Hbb th3/+ mice significantly improved iron overload and anemia, corroborating the notion that increased hepcidin activity could be beneficial in this disorder. 158 In fact, in Hbb th3/+ mice, use of both antisense oligonucleotide (Tmprss6-ASO) and RNA interference (Tmprss6-siRNA) can reduce the synthesis of transmembrane serine protease Tmprss6 by degrading the corresponding mRNA. This led to increased hepcidin expression, decreased Tf-sat and reduction of hemichrome formation and apoptosis in erythroid cells.…”
Section: Tmprsss6 Inhibitorsmentioning
confidence: 99%
“…Targeting TMPRSS6: Nai et al 59 demonstrated that homozygous inactivation of TMPRSS6 in thalassemic th3/+ mice increased hepcidin levels, ameliorated iron overload, and improved ineffective erythropoiesis. The study provided the proof of principle that targeting of Tmprss6, a negative regulator of hepcidin production, may be a useful approach for the therapy of iron overload disorders.…”
Section: Class 2: Stimulators Of Hepcidin Productionmentioning
confidence: 99%